(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
As a representative figure of Soviet rural literature, Kyrgyz writer Chinghiz Aitmatov takes his native village Sheker as his spiritual origin. Adopting artistic conventional devices such as myths and symbols, he depicts national memory, ecological ethics and universal human moral ideals. Chi Zijian, a core writer of Chinese root-seeking literature, is deeply influenced by Aitmatov’s works. Taking Arctic Village, the Greater Khingan Mountains and the Ewenki ethnic civilization as writing carriers, she traces local cultural origins through folk legends and primitive natural scenes. The two writers form a cross-national and cross-civilizational typological literary resonance: both regard their hometowns as spiritual coordinates and reflect on ecological crises through poetic rural depictions; both employ mythic narratives to carry collective clan memory and criticize the modern dilemma of abandoning traditions and severing cultural roots; both center on grassroots laborers and adhere to the core creative tenet of moral idealism. By comparing their textual motifs, artistic techniques and value stances, this paper explores the shared spiritual pursuits of cross-cultural rural literature and provides references for comparative studies on rural and root-seeking literature between China and Russia.